Explaining the Impact of Marketing Items on Post-Consumer Behavior in Russian Consumer Society Based on Supply Chain Management - Diana Stepanova; Larisa Makhova; Alexander Biryukov (International Journal of Supply Chain Management, 2018)
Postmodernism is a variety of meanings and definitions, is used to refer to many aspects of social life from musical forms and styles, literature and fine art through to philosophy, history and especially the mass media and consumer culture. Postmodernism is a slippery term that is used by writers to refer to several different things. In addition, post modernism and profound changes in marketing requirements has great impact on consumer society. The consumer plays a significant role in the demand andsupply chain for every economic system. The purpose of this study is to explain the impact of motivation, perception, attitudes of post-modern consumer and post-modern marketing on post-consumer behavior based on supply chain management. This research is applied in terms of its purpose while, in terms of collecting information, it is a descriptive study. The statistical population of the research is Russian consumer society. The statistical population of the research is Russian consumer society. According to the Cochran formula, an estimated 384 individuals from this population were selected randomly with an estimated error of 0.5 and self-confidence of 0.95. The data collection tool is a questionnaire designed by the researcher. For Cronbach's alpha, the reliability is 0.95. For analyzing the data and measuring the impact of the model variables, a structural equation model was used with Imus software. The results of this study indicate confirmation of the impact of the variable of motivation, perception, attitudes of the post-modern consumer, and finally the effect of post-modern marketing on post-consumer behavior. Key words post-consumer behavior, motivation, perception, attitudes of post-modern consumer, post-modern marketing, supply chain management